Synthesis and characterization of Na2O-CaO-SiO2 glass-ceramic - Kaygili, Omer (Springer, 2014)
The Na2O-CaO-SiO2 ternary glass-ceramic with the composition of 49 mass% Na2O, 20 mass% CaO, and 31 mass% SiO2 was prepared by the conventional method. The ternary glass-ceramic was characterized using X-ray diffraction (XRD), differential thermal analysis (DTA), thermogravimetric analysis, Fourier transform infrared spectroscopy, and scanning electron microscopy techniques. The Na2CaSiO4 phase, having the cubic crystal system, with the crystallite size of 25.14 nm and lattice parameter of 0.7506 nm was determined from the XRD pattern. The activation energy of the glass-ceramic calculated from the DTA curves was found to be 162.02 kJ mol(-1). The Avrami exponent was found to be similar to 2 indicating a one-dimensional growth process. The mass loss percent from ambient temperature to 1,173 K is less than 1 %. The density was calculated to be 2,723 kg m(-3). The fine-grained microstructure with the particle sizes less than 1 mu m was confirmed by the scanning electron microscope micrograph.
Keywords: Glass-ceramic; Na2O-CaO-SiO2; Avrami exponent; Activation energy